Pengaruh Customer Experience, Trust dan Brand Image terhadap Minat Beli Ulang Paket Internet Smartfren - Khatimah, Anik Khusnul; Sudarwati, Sudarwati; Hamidah, Raisa Aribatul (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
There are various internet package providers that trigger competition between providers which makes producers compete to set strategies so they can win the competition. There are several factors to consider for consumers to repurchase a product including customer experience, consumer trust and brand image. the purpose of this study to determine the effect of customer experience, trust and brand image on the intention to repurchase internet packages in Karanganyar. in this study using quantitative research methods. Population used are smartfren internet package users in Karanganyar who use it more than once, the number of which cannot be known and is included in the unlimited population category, the sample used is 100 respondents. Targeted sampling methods that use low-probability sampling techniques. The data collection used consists of observations, documentation, questionnaires, interviews and literature research. Data analysis techniques include statistical analysis such as multiple regression test, F-test, T-test, and coefficient of determination. The results of this survey have a positive and significant impact on the intention to purchase Smartfren internet packages in Karanganyar. Keyword : Customer Experience, Trust, Brand Image, repurchase intention.